Detection of SARS‐CoV‐2 in different human biofluids using the loop‐mediated isothermal amplification assay: A prospective diagnostic study in Fortaleza, Brazil. Issue 9 (20th May 2022) - Clementino, Marco; Cavalcante, Karene F.; Viana, Vania A. F.; Silva, Dayara de Oliveira; Damasceno, Caroline R.; Fernandes de Souza, Jessica; Gondim, Rafhaella N. D. G.; Jorge, Daniel M. de Melo; Magalhães, Lyvia M. V. C.; Arruda, Érico A. G. de; Neto, Roberto da J. P.; Medeiros, Melissa S.; et al.
Abstract: We adopted the reverse‐transcriptase‐loop‐mediated isothermal amplification (RT‐LAMP) to detect severe acute respiratory syndrome coronavirus 2 (SARS‐Cov‐2) in patient samples. Two primer sets for genes N and Orf1ab were designed to detect SARS‐CoV‐2, and one primer set was designed to detect the human gene Actin . We collected prospective 138 nasopharyngeal swabs, 70 oropharyngeal swabs, 69 salivae, and 68 mouth saline wash samples from patients suspected to have severe acute respiratory syndrome (SARS) caused by SARS‐CoV‐2 to test the RT‐LAMP in comparison with the gold standard technique reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR). The accuracy of diagnosis using both primers, N5 and Orf9, was evaluated. Sensitivity and specificity for diagnosis were 96% (95% confidence interval [CI]: 87–99) and 85% (95% CI: 76–91) in 138 samples, respectively. Accurate diagnosis results were obtained only in nasopharyngeal swabs processed via extraction kit. Accurate and rapid diagnosis could aid coronavirus disease 2019 (COVID‐19) pandemic management by identifying, isolating, and treating patients rapidly.